Field geology, petrology and geochronology of pluton-dyke systems, the Trapecio and Ushuaia Peninsula dyke swarms (Fuegian Andes): Emplacement conditions and relation with tectonics - Gonzalez Guillot, Mauricio Alberto; Torres Carbonell, Pablo Juan; Cao, Sebastián José; Lobo, Constanza; Bordese, Sofía; Hollanda, María Helena B.M. (Journal of the Geological Society)
We report the field geology, petrography, geochemistry and geochronology data for two dyke swarms in the Fuegian Andes, with the aim of correlating them with known suites and of improving the knowledge on the magmatism of the Late Cretaceous rear-arc and its relation with ductile deformation. We also provide keys for correlation based on amphibole K2O content. The Trapecio dyke swarm is mildly alkaline and ferriferous, with a zircon U-Pb age of 75 Ma; thus it belongs to the Fuegian Potassic Magmatism (78-68 Ma). The Ushuaia Peninsula dyke swarm, also known as Ushuaia Peninsula Andesites (UPA), was shown to be high-K calc-alkaline and magnesian. New radiometric ages gave 87-86 Ma. While the UPA dyke swarm exhibits foliation associated with ductile deformation, the Trapecio dyke swarm is post-kinematic and reveals emplacement controlled by the slaty cleavage in the metapelite host. Field and geophysical evidence suggest both swarms overlie small upper-crustal plutons, mostly buried. The variable composition of dykes suggests a protracted history of dyke injection, mostly fed from deeper reservoirs. Contact metamorphism around both pluton-dyke systems is very weak. By comparison with adjacent plutons we argue that the main variables controlling aureole development are small magma volumes and low injection rates. Fil: Gonzalez Guillot, Mauricio Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina Fil: Torres Carbonell, Pablo Juan. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Cao, Sebastián José. Universidad Nacional de Tierra del Fuego. Instituto de Ciencias Polares, Recursos Naturales y Ambiente; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias ...